Analisis Faktor- Faktor Yang Mempengaruhi Keputusan Mahasiswa Memilih Kuliah Di STKIP NASIONAL - Roza, Silvia; Sumarni, Sumarni; Refinaldi, Refinaldi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Nasional, 2021)
Abstract This research is motivated by how a person acts in making decisions to choose a place to study with various considerations, whether by looking at the brand image, location education costs or promotions carried out by a campus in attracting students. This study aims to find the extent of the influence of education costs, brand image, location and promotion of the decision of students choosing to study at the National STKIP. The type of research used in this study is correlation. The population in this study was 440 people with 209 Proposional Random Sampling sampling techniques. Data collected by descriptive analysis and prerequisite test analysis. The results of the descriptive analysis are in the quantitative category both in the amount of 72.42 and partially the education costs of education, brand image, location and promotion have a significant positive effect on the decision of students to choose to study at STKIP Nasional. Then the results of simultaneous data analysis of education costs, brand image, location and promotion show the number 0.172 or 17.2%.